Nonlinearities in the relationship between debt and growth: (no) evidence from over two centuries - Eberhardt, Markus (Cambridge University Press, 2017)
I revisit the popular concern over a nonlinearity or threshold in the relationship between public debt and growth employing long time series data from up to 27 countries. My empirical approach recognises that standard time series arguments for long-run equilibrium relations between integrated variables (cointegration) break down in nonlinear specifications such as those predominantly applied in the existing debt-growth literature. Adopting the novel co-summability approach my analysis overcomes these difficulties to find no evidence for a systematic long-run relationship between debt and growth in the bivariate and economic theory-based multivariate specifications popular in this literature.